2022
DOI: 10.3389/fendo.2022.869128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Interventional Exercise Programme on Muscle Strength, Mobility and Fitness in Patients With Diabetic Foot in Remission: Results From BIONEDIAN Randomised Controlled Trial

Abstract: ObjectivesDiabetic foot syndrome (DFS) is a serious late diabetic complication characterised by limited joint mobility and other biomechanical and muscle abnormalities.AimTo evaluate the effect of an interventional exercise programme on anthropometric parameters, muscle strength, mobility and fitness in patients with diabetic foot in remission.Data Sources and Study SelectionThirty-eight patients with type 2 diabetes and DFS without active lesions (mean age 65 ± 6.9 years, BMI 32 ± 4.7 kg.m-2, waist-hip ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…In 1 other RCT, physical activity was measured using a questionnaire. 24 Vratna et al found a statistically significantly larger increase in high-and moderate-intensity physical activity in the intervention group, compared to the control group. 24 In secondary analyses, LeMaster et al 13 found in the 23 (29%)…”
Section: Weight-bearing Activitymentioning
confidence: 95%
See 4 more Smart Citations
“…In 1 other RCT, physical activity was measured using a questionnaire. 24 Vratna et al found a statistically significantly larger increase in high-and moderate-intensity physical activity in the intervention group, compared to the control group. 24 In secondary analyses, LeMaster et al 13 found in the 23 (29%)…”
Section: Weight-bearing Activitymentioning
confidence: 95%
“…Summary of the literature: We identified 5 RCTs with a combined total of 274 participants (Figure 2) reporting ulcer incidence during a foot-ankle exercise programme that met the criteria for metaanalysis. 5,10,13,14,24 In the meta-analysis (Figure 2 van NETTEN ET AL.…”
Section: Foot Ulcers and Pre-ulcerative Lesionsmentioning
confidence: 99%
See 3 more Smart Citations